Section 5: Decision Support, Knowledge Representation and Management: Decision support, Knowledge Representation and Management: A broad methodological spectrum - Brigl, B.; Managing Editor for the IMIA Yearbook Section on Decision Support, Knowledge Representation and Management. (Yearbook of Medical Informatics, 2006)
To summarize current excellent research in the field of decision support, knowledge management and representation.Synopsis of the articles selected for the IMIA Yearbook 2006.Decision Support, Knowledge Representation and Management covers a broad spectrum of methods applied to a variety of medical problems and domains. Some particularly interesting and current topics were picked for the IMIA Yearbook 2006: the importance of ontologies for systematic system engineering of decision support systems, syndromic surveillance based on natural language processing, the evaluation of large semantic networks, and a comprehensive ontology for a randomised controlled trial database to support evidence-based practise.The best paper selection shows that methods for decision support, knowledge representation and management can decisively contribute to the solution of many different medical problems, but also that there is still a lot of exiting research to be done
Keywords: Medical Informatics; International Medical Informatics Association; Yearbook; knowledge management; knowledge representation; decision support; ontologies; natural language processing